Effect of dietary addition of unprocessed, autoclaved or pre germinated fenugreek seeds on laying hens’ performance and egg quality - Omri, Besma; Chalghoumi, Raja; Abdouli, Hédi (Revista Colombiana de Ciencias Pecuarias, 2017)
Background: previous studies have shown that fenugreek seed given at 6 g/hen/d in an attempt to reduce yolk cholesterol tended to reduce laying performance and that autoclaving and pre-germination improved its in vitro nutritional values. Objective: to evaluate the effect of dietary addition of unprocessed (UPFS), autoclaved (AFS) or pre-germinated (PGFS) fenugreek seeds on laying hens’ performance, egg physical characteristics and chemical composition. Methods: forty-eight 31 week-old Novogen white laying hens were divided into four groups and given 100 g/hen/d of a basal diet containing 0 (control) or 5.7 g of UPFS, AFS, or PGFS during nine weeks. Repeated and non-repeated data were analyzed using the Mixed and GLM procedures, respectively. Results: diet, week on diet and their interaction affected consumption (p<0.05). Laying rate was not affected (p>0.05) by week on diet but was reduced (p<0.05) by UPFS-diet. Moreover, UPFS-diet reduced (p<0.05) daily egg mass production. Feed conversion ratio was not affected (p>0.05) by dietary treatment or by week on diet. Egg, yolk, albumen and shell weights were affected (p<0.05) by week on diet but not by diet nor diet-week interaction. Dietary inclusion of fenugreek seeds did not affect total egg crude protein, yolk lipids, and triglyceride nor yolk cholesterol contents. Conclusion: unprocessed fenugreek reduced laying rate and daily egg mass production, but these effects were removed by autoclaving or pre-germination. Further investigations are needed to evaluate the impact of fenugreek seeds dietary supplementation on fatty acids profile and lipid peroxidation.